2020
DOI: 10.1155/2020/9765950
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cellulose from Wheat Straw Using Alkaline Hydrogen Peroxide and Acidified Sodium Chlorite Treatments: Comparison of Yield and Properties

Abstract: Environmental concerns due to excessive use of synthetic or petroleum-based materials have encouraged scientists to develop novel, sustainable, and multifunctional material using abundant lignocellulosic biomass. In this work, a study was conducted on the isolation of cellulose from wheat straw using two different methods: acidified sodium chlorite and alkaline hydrogen peroxide. A comparative study was carried out based on the yield and properties of extracted cellulose. The final product (after treatments) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Table 2 shows the relationships between NaOH concentration, reaction time, and temperature with lignin, In general, the data in Table 2 show that the sample at low temperature (23 °C) and short reaction time (2 hours) had the highest lignin (12:3 ± 0:12 wt%) and hemicellulose content (20:45 ± 0:17 wt%) and the lowest cellulose content (55:44 ± 0:25 wt%) than other samples (6R24, 5R24, 6SF3, 6EF3, 4EN3, 5EN3, 6EN2, 6EN3, and 6EN4). The white color of the bleached sample showed that the noncellulosic components (lignin and hemicellulose) have been eliminated from the fiber [54]. Thus, the color changes due to chemical treatment, indicating that some fiber components have been removed from OA fibers.…”
Section: Alkaline Treatmentmentioning
confidence: 99%
“…Table 2 shows the relationships between NaOH concentration, reaction time, and temperature with lignin, In general, the data in Table 2 show that the sample at low temperature (23 °C) and short reaction time (2 hours) had the highest lignin (12:3 ± 0:12 wt%) and hemicellulose content (20:45 ± 0:17 wt%) and the lowest cellulose content (55:44 ± 0:25 wt%) than other samples (6R24, 5R24, 6SF3, 6EF3, 4EN3, 5EN3, 6EN2, 6EN3, and 6EN4). The white color of the bleached sample showed that the noncellulosic components (lignin and hemicellulose) have been eliminated from the fiber [54]. Thus, the color changes due to chemical treatment, indicating that some fiber components have been removed from OA fibers.…”
Section: Alkaline Treatmentmentioning
confidence: 99%
“…FTIR spectra (wheat straw and cellulose) in Figure 1A showed the absorbance peaks of cellulose OH at 3400 cm −1 and for CH group stretching at 2900 cm −1 (Table S4). [ 24 ] The bending vibrations of CH (1300 cm −1 ) and CH 2 (1430 cm −1 ) of cellulose were present in wheat straw and cellulose. The peak at 895 cm −1 assigned to β‐gycosidic linkage and the water absorption peak at 1644 cm −1 were present in the spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The increment in degradation and decomposition temperature may be attributed to the removal of lignin and hemicellulose. [24,32] Figure 1D shows the surface morphology of extracted cellulose from wheat straw.…”
Section: Structural and Thermal Stabilitymentioning
confidence: 99%
“…Then the remnant is washed with distilled water till all the traces of chemicals are removed and the pH of the residue is neutral. The residue is then strained and desiccated in the oven at 75°C for further use 57,58 Flowchart 4 highlights the extraction steps of this process.…”
Section: Methodsmentioning
confidence: 99%